Socioeconomic factors influencing farmers' adoption of alley farming technology under intensified agriculture in Imo State, Nigeria - Onu, Donatus Orji (2006)
The socioeconomic factors influencing farmers' alley farming technology adoption behaviors in the intensified land use systems of Imo State, Nigeria were studied. A logit econometric model was used to quantity and analyze data obtained from 480 randomly selected farm households from 12 agriculturally intensified autonomous communities in Imo State. The results showed that younger farmers aged 18-44, cultivating at least 0.7 ha of land, over which they have control in terms of allocation and usage, had higher probabilities of adopting alley farming technology compared to the older farmers. Adoption decisions increased with increased contacts of farmers with extension agents working on the agroforestry technology, farmers' level of formal education, ownership and control over cultivated lands, length of land lease, membership and participation in the activities of farmers' associations and farm sizes greater than the sample mean farm size of 0.7 ha. Adoption rates were lower among female farmers than male farmers, and decreased with increased family size and population-induced land scarcity conditions. The study confirms the importance of recognizing the heterogeneity of the farming population not only in terms of differences in the biophysical conditions of their farms but also in the terms of the socioeconomic and demographic conditions under which they operate, in targeting agroforestry extension programs for maximum impact.
Keywords: Farmers' attitudes; Agricultural technology; Sociocultural factors